2011
DOI: 10.1124/dmd.111.041293
|View full text |Cite
|
Sign up to set email alerts
|

The Proton Pump Inhibitor, Omeprazole, but Not Lansoprazole or Pantoprazole, Is a Metabolism-Dependent Inhibitor of CYP2C19: Implications for Coadministration with Clopidogrel

Abstract: ABSTRACT:As a direct-acting inhibitor of CYP2C19 in vitro, lansoprazole is more potent than omeprazole and other proton pump inhibitors (PPIs), but lansoprazole does not cause clinically significant inhibition of CYP2C19 whereas omeprazole does. To investigate this apparent paradox, we evaluated omeprazole, esomeprazole, R-omeprazole, lansoprazole, and pantoprazole for their ability to function as directacting and metabolism-dependent inhibitors (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 39 publications
12
70
2
Order By: Relevance
“…The time-dependent shift in IC 50 with (S)-mephenytoin described above is consistent with the observations of Ogilvie et al (2011) and Boulenc et al (2012). In fact, both groups have reported omeprazole (up to 100 M) as a mechanism-based inhibitor of CYP2C19 in HLM and reported K I values ranging from 1.7 to 9.1 M and k inact values ranging from 0.016 to 0.046 min Ϫ1 .…”
Section: Reversible Inhibition Of P450s In the Absence Of Preincubatisupporting
confidence: 77%
See 2 more Smart Citations
“…The time-dependent shift in IC 50 with (S)-mephenytoin described above is consistent with the observations of Ogilvie et al (2011) and Boulenc et al (2012). In fact, both groups have reported omeprazole (up to 100 M) as a mechanism-based inhibitor of CYP2C19 in HLM and reported K I values ranging from 1.7 to 9.1 M and k inact values ranging from 0.016 to 0.046 min Ϫ1 .…”
Section: Reversible Inhibition Of P450s In the Absence Of Preincubatisupporting
confidence: 77%
“…During the course of the study, it was evident that some of the PPIs behaved as relatively potent inhibitors of CYP2C19 (versus other P450s) and two of them (omeprazole and esomeprazole) also behaved as time-dependent inhibitors. The latter result supports the findings of Ogilvie et al (2011) and Boulenc et al (2012), and the more recent findings of Ohbuchi et al (2012) using 2-oxo-clopidogrel as substrate. Additional studies were conducted with recombinant CYP2C19 (rCYP2C19) using three different substrates , (S)-mephenytoin, and diazepam] and with serum-coincubated human primary hepatocytes using diazepam as substrate.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…To the best of our knowledge, no specific data on the interaction between PPIs and acenocoumarol are available. In a recent in vitro study, esomeprazole and omeprazole were considered as irreversible CYP2C19 inhibitors [37]. Moreover, in a crossover clinical study, a significant DDI was observed between high doses of omeprazole and clopidogrel in healthy subjects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Based on in vitro and in vivo data, omeprazole and esomeprazole are the most potent CYP2C19 inhibitors [69]. In vivo, omeprazole and esomeprazole induced 4 and 10 fold functional inhibition of CYP2C19 versus less than 1.5 fold inhibition with lansoprazole and pantoprazole [70]. Rabeprazole has in vitro data showing less inhibition of CYP2C19 than omeprazole and lansoprazole but no in vivo data is available [69].…”
Section: Drug Interactions Impeding Cardiovascular Drug Functionmentioning
confidence: 99%